Osteoid Osteoma Invading the Posterior Labyrinth of the Petrous Bone - Dugert, E.; Lagleyre, S.; Brouchet, A.; Deguine, O.; Cognard, C.; Bonneville, F. (American Journal of Neuroradiology, 2010)
SUMMARY: We report a painless osteoid osteoma of the inner ear in an elderly woman presenting with hearing loss, tinnitus, and vertigo. CT showed a heterogeneous mass containing calcifications involving the posterior labyrinth, which heterogeneously enhanced on postcontrast MR images. Osteoid osteoma should be included in the differential diagnosis of an osteolytic petrous bone lesion with central calcification and enhancement. OOosteoid osteoma